Functional analysis of the cysteine synthase protein complex from plants: structural, biochemical and regulatory properties - Wirtz, Markus; Hell, Rüdiger (Journal of plant physiology, 2006)
Summary: Cysteine synthesis in plants represents the final step of assimilatory sulfate reduction and the almost exclusive entry reaction of reduced sulfur into metabolism not only of plants, but also the human food chain in general. It is accomplished by the sequential reaction of two enzymes, serine acetyltransferase (SAT) and O-acetylserine (thiol) lyase (OAS-TL). Together they form the hetero-oligomeric cysteine synthase complex (CSC). Recent evidence is reviewed that identifies the dual function of the CSC as a sensor and as part of a regulatory circuit that controls cellular sulfur homeostasis. Computational modeling of three-dimensional structures of plant SAT and OAS-TL based on the crystal structure of the corresponding bacterial enzymes supports quaternary conformations of SAT as a dimer of trimers and OAS-TL as a homodimer. These findings suggest an overall α6β4 structure of the subunits of the plant CSC. Kinetic measurements of CSC dissociation triggered by the reaction intermediate O-acetylserine as well as CSC stabilization by sulfide indicate quantitative reactions that are suited to fine-tune the equilibrium between free and associated CSC subunits. In addition, in vitro data show that SAT requires binding to OAS-TL for full activity, while at the same time bound OAS-TL becomes inactivated. Since OAS concentrations inside cells increase upon sulfate deficiency, whereas sulfide concentrations most likely decrease, these data suggest the dissociation of the CSC in vivo, accompanied by inactivation of SAT and activation of OAS-TL function in their free homo-oligomer states. Biochemical evidence describes this protein-interaction based mechanism as reversible, thus closing the regulatory circuit. The properties of the CSC and its subunits are therefore consistent with models of positive regulation of sulfate uptake and reduction in plants by OAS as well as a demand-driven repression/de-repression by a sulfur intermediate, such as sulfide.